World Heritage and the challenge of climate change: a reform agenda. Issue 1 (1st February 2023) - Marsh, Helene; Smith, Anita; Terrill, Greg
ABSTRACT: The General Assembly of States Parties to the World Heritage Convention adopted a policy and strategy on climate change in 2007. Many of its actions remain to be delivered. Climate change has highlighted the limits of a system under stress to respond to an immense challenge. The General Assembly is again considering the issue, and a second World Heritage climate change policy is being developed to provide high-level guidance on response measures. The draft second policy emphasises the role of individual States Parties in addressing climate impacts on their World Heritage sites but says less about the responsibilities of the World Heritage Committee, World Heritage Centre or Advisory Bodies to the Convention in meeting the goals of climate action and achieving an equitable, international and shared response. Nor does it tackle issues related to Outstanding Universal Value, the core of any response to climate change. We develop a conceptual framework for substantive reform and propose actions to enable the World Heritage system to effectively respond to climate change and support the resolution of longstanding, systemic issues. Meaningful response to climate change needs to involve strategic as well as operational elements in a staged response with measurable outcomes and outputs.